New records of wood inhabiting fungal species from Kondapalli reserved forest of Central Eastern Ghats, India - Nagadesi, Praveen Kumar; Rampilla, Venkatesh (Plant Science Today, 2021)
Wood inhabiting fungi that grow specifically on leaf litter, wood debris, humus rich soil of forest helps in biodegradation and increase soil fertility. The fruiting bodies of fungi were collected from partially dead forest trees, fallen wooden logs, leaf litter and decomposing humus rich soil of Kondapalli forest area, Central Eastern Ghats of India. Detailed macroscopic and microscopic study of collected fungal samples revealed the occurrence of wood inhabiting fungi belonging to 7 genera and 9 species; i.e. Geastrum triplex Jungh., Marasmius siccus (Schweinitz) Fries, M. fulvoferrugineus Gilliam, M. oreades (Bolt.: Fries) Fries Epicr. Lactarius piperatus (L.) Pers., Flammulina velutipes (Curtis) Singer, Artomyces microsporus (Qiu X. Wu & R. H. Petersen) Lickey, Hymenochaetopsis rigidula (Berk. & M. A. Curtis) S. H. He & Jiao Yang and Bjerkandera adusta (Willd: Fr.) Karst. For the first time, A. microsporus (Qiu X. Wu & R. H. Petersen) Lickey and H. rigidula (Berk. & M. A. Curtis) S. H. He & Jiao Yang., were reported from India. M. fulvoferrugineus Gilliam was reported second time from India. The wood inhabiting fungi were new records to Kondapalli forest area, Central Eastern Ghats of India.